Correlation between sliding bearing wear rate and material characteristics of friction surfaces in heavily loaded construction and road machinery - Shchukin, O.; Orel, O.; Kholodov, A.; Kravets, A.; Fedoriachenko, S. (Problems of Tribology, 2026)
Based on an investigation of how entropy generation depends on material and tribological characteristics, it was found that the wear rate of a sliding bearing operating under elastic and elastoplastic contact conditions exhibits a nonmonotonic relationship with the surface dislocation density. Specifically, at relatively low dislocation densities, wear intensifies as this parameter increases, whereas in the high-density regime, further growth leads to a reduction in wear. A mathematical model describing entropy generation arising from the interaction between lubricant molecular dipoles and dipoles induced by fluctuations in surface dislocation density has been derived. The results demonstrate that the component of wear associated with this mechanism of entropy production decreases as the dipole moment of the lubricant molecules increases. An additional analysis focusing on the influence of material parameters on entropy generation shows that bearing wear intensity rises with increasing surface dislocation density. An analytical expression for entropy production due to fluctuations in surface dislocation density has been obtained. It is also established that, for the crankshaft sliding bearing of the DZk-250 motor grader operating under elastoplastic contact conditions, the wear intensity follows a similar trend: it increases with growing surface dislocation density in the low-value range and decreases when this parameter reaches higher values. Furthermore, an equation describing entropy generation during the interaction between lubricant molecular dipoles and dipoles associated with dislocation density fluctuations has been formulated.